Effect of exposure from iPhone 12 on programmable ventriculoperitoneal shunts. (4th May 2022) - Kumar, Ameeta; Pervaiz, Arbaaz; Borg, Anouk; Abdul-Hamid, Ayeshah; Jeyaretna, Sanjeeva; MacKeith, Samuel; Qureishi, Ali
Abstract: The latest iPhone 12 model has elicited concerns over its interaction with medical devices such as pacemakers due to its integrated MagSafe technology. Historically, programmable ventriculoperitoneal (VP) shunts have been demonstrated to readjust when exposed to magnetic objects. Yet, the presence of interactions between the iPhone 12 and shunts is unknown. In this in-vitro study, we examined the effect on the programming of three VP shunts, Medtronic Strata II, Miethke ProGAV 2.0 and Codman Hakim, when exposed to the iPhone 12 model. We found that all three valves did not re-program when the iPhone was held near or moved in a swiping or rotational motion above the valves. Therefore, the risk of re-programming of these three shunts when exposed to iPhone 12 appears to be low. However, patients should take care until further work is undertaken to examine the complex interplay between programmable VP shunts with magnetic devices.